Pengaruh Tingkat Pertumbuhan Penjualan dan Perputaran Piutang Terhadap Likuiditas Perusahaan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2012-2014 - Indrayenti INDRAYENTI; Siska Natania (Universitas Bandar Lampung (UBL), 2016)
This study is to identify and analyze the effect of growth sales rate and receivable turnover on liquidity in the manufacture companies listed in Indonesia Stock Exchange period 2012-2014. The first hypothesis is growth sales rate has effect on liquidity and the second hypothesis is receivable turnover has effect on liquidity. The sample in this study is the manufacture companies consumer goods sector listed in Indonesia Stock Exchange period 2012-2014. Sampling technique used in this study is purposive sampling, so that obtained 21 companies. Analyze technique used in this study is multiple linier regression analyze. Hypothesis test is using t-test and coefficient of determination. The classic assumption which consist of normality test, multicolinearity test, heteroskedasticity test, and autocorrelation test is also being done in this study. The results showed that growth sales rate has significant positive influence on liquidity in the manufacture companies consumer goods sector listed on the Indonesia Stock Exchange amd receivable turnover has significant positive influence on liquidity in the manufacture companies consumer goods sector listed in Indonesia Stock Exchange.